Assessing the decentralization transition in Libya: causes, consequences and challenges (Journal of Academic Research, 2024)
AbstractThe transition to decentralization in the management of Public Affairs has become an urgent demand of democracy in the lives of people. It is, also, important to enhance the efficiency and effectiveness of Public Administration in Libya. Despite the reasons that call for decentralization, such as increasing transparency and accuracy of accountability for those who take care of Public Affairs at the local level, this process is not done easily and conveniently. This study aims to assess the process of decentralization in Libya by seeking opinions of a sample of (250) individuals who hold administrative positions and memberships of municipal councils in the public sector in three main regions: the West, the South and the East. The evaluation process was carried out in three main areas: the reasons for decentralization, the expected results of decentralized administration, and the challenges faced by the decentralization process in Libya. The validity and reliability of the questionnaire were verified. Statistically significant results were valid reasons for decentralization in Libya, expected positive outcomes from the decentralization process, and the existence of challenges facing the decentralization process. The most important recommendations were to carry out economic and social studies related to local affairs, distribute resources efficiently if responsibility for public spending is entrusted to the local government level, overcome the difficulties facing the collection of taxes and fees, and develop clear and transparent mechanisms to obtain support from the central government.Key words: Libya, Local Administration, Central Government, Decentralization: reasons, results and challenges.